ANALISIS PENERAPAN PP NO. 71 TAHUN 2010 TENTANG STANDAR AKUNTANSI PEMERINTAH PADA KANTOR KECAMATAN PONTIANAK SELATAN - B51112051, Marhaini Novita Nababan (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
The Governmental Accounting Standards (GAS) are the principles of accounting implemented in assembling and presenting the governmentâ€™s financial report. This study aims to find out and to analyse the implementation of Government Regulation No. 71 of 2010 on The Governmental Accounting Standards in South PontianakÂ  Sub-district Office and all the obstacles experienced. This research belongs to descriptive qualitative research. The data were collected by interviewing and library research. The data analysis technique used was descriptive method by comparing the theory and regulations with the factual condition. Then the results were reviewed, analysed and concluded. In this method, the researcher used qualitative analysis by comparing the current financial report with the governmental accounting standards set in Government Regulation No. 71 of 2010 as the guidance in the preparation of government financial report.